Melatonin Regulates Differentiation of Sheep Brown Adipocyte Precursor Cells Via AMP-Activated Protein Kinase - Gao, Xu-Yang; Deng, Bu-Hao; Li, Xin-Rui; Wang, Yu; Zhang, Jian-Xin; Hao, Xiao-Yan; Zhao, Jun-Xing (Frontiers in Veterinary Science, 2021)
In sheep industry, hypothermia caused by insufficient brown adipose tissue (BAT) deposits is one of the major causes of lamb deaths. Enhancing the formation and function of BAT in neonatal lamb increases thermogenesis and hence reduces economic losses. The aim of the present study was to explore the effect and mechanism of melatonin on sheep brown adipocyte formation and function. Sheep brown adipocyte precursor cells (SBACs) isolated from perirenal BAT were treated with melatonin (1 nM and 10 nM). The SBACs subjected to melatonin exhibited a decreased proliferation ability, accompanied by down-regulated proliferating cell nuclear antigen, cyclin D1 and CDK4 protein contents in a melatonin dose dependent manner. Melatonin promoted brown adipocytes formation and induced the expression of brown adipogenic markers, including uncoupling protein 1 and PR domain-containing 16 during differentiation of SBAC. Moreover, the AMP-activated protein kinase α1 (AMPKα1) activity was positively correlated with brown adipocytes formation potential. Importantly, melatonin effectively activated AMPKα1. Furthermore, promotional effects of melatonin were abolished by AMPKα1 knockout, suggesting the involvement of AMPKα1 in this process. Collectively, these results suggested that melatonin enhanced brown adipocytes formation in sheep brown adipocyte precursor cells in vitro through activation of AMPKα1.